TIJORAT BANKLARIDA NAQD PULSIZ OPERATSIYALAR HISOBI VA UNI TAKOMILLASHTIRISH YO’LLARI - Fayzullaeva Saida Asatullaevna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, the payment system of the Republic of Uzbekistan and the role of cashless payments in it, settlement operations in the activity of commercial banks, and methodological foundations of the interbank payment system of the Central Bank are explained theoretically. Also, the analysis of the mechanism of organization of non-cash payments in commercial banks, the mechanism of organization of non-cash payments in commercial banks, modern forms of organization of non-cash payments in commercial banks are given.